PENGARUH STRATIFIKASI SOSIAL TERHADAP TOKOH PIP DALAM NOVEL GREAT EXPECTATIONS KARYA CHARLES DICKENS - ALIWU, SUNARTI (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2016)
Abstract This research is entitled â€œThe Influence of Social Stratification on Pip in novel Great Expectations by Charles Dickensâ€. This study discusses about meaning of the social stratification and influence on Pip in novel Great Expectations. The aim of this study is to know the meaning and the influence of social stratification on Pip that gives some impacts to his life which change his personality and attitude. This study applies intrinsic and extrinsic approaches by Wellek and Warren (1949). In analyzing the influence of social stratification on Pip, the writer uses theories by Sorokin (1969) and Weber (cited in Ilmusiana, 2015). This study also uses descriptive method in analyzing the data. The result shows that the main character Pip became a different person because of the influence of social stratification. The background of his family from the low class society makes him want to be a man of high class and rich. Estella makes Pip fall in love when he was a child and this encourages him to change his life. Pipâ€™s live begins when he lives in London and leaves his family in the village. The riches he receives from the benefactor make him arrogant but later Pip regrets